Local Wisdom Pikukuh Sapuluh Suku Baduy Dalam Konservasi Lingkungan Budaya Desa Kanekes - Halmahera, Mega; Purnama, Anggi Septiya; Hasyim, Fuad; Benardi, Andi Irwan (Geo-Image, 2019)
Baduy tribe is in Kanekes Village, Leuwidamar Subdistrict, Lebak Regency, Banten. The tribe that lives depends on nature and always maintains the balance of nature, through traditional rules and pikukuh sapuluh is the basis of life guidelines and produces Baduy culture both in thinking, acting and behaving. The study,